2018
DOI: 10.1007/s00167-018-5007-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased fatigue of the biceps after tenotomy of the long head of biceps tendon

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…According to the Hamada classification, the statistical difference between groups 1, 2 and 3 was evident, with predominance of the presence of the long head of the biceps, and groups 4a, 4b and 5 with predominance of its absence. This result may have contributed to the best functional outcomes of groups 1, 2 and 3; therefore, considering the evolutionary aspect of the Hamada classification, the long head of the biceps could act as a humeral head depressor and prevent the progression of arthropathy, as evidenced by Garcia et al 14 in their 2018 study. Regarding the subscapular tendon, there was no statistically significant difference among the groups ( Table 2 ), which leads to the belief that this parameter did not influence the functional results in the studied shoulders.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…According to the Hamada classification, the statistical difference between groups 1, 2 and 3 was evident, with predominance of the presence of the long head of the biceps, and groups 4a, 4b and 5 with predominance of its absence. This result may have contributed to the best functional outcomes of groups 1, 2 and 3; therefore, considering the evolutionary aspect of the Hamada classification, the long head of the biceps could act as a humeral head depressor and prevent the progression of arthropathy, as evidenced by Garcia et al 14 in their 2018 study. Regarding the subscapular tendon, there was no statistically significant difference among the groups ( Table 2 ), which leads to the belief that this parameter did not influence the functional results in the studied shoulders.…”
Section: Discussionmentioning
confidence: 89%
“…Segundo a classificação de Hamada, ficou evidente a diferença estatística entre os grupos 1, 2 e 3, com predominância de presença da cabeça longa do bíceps, e os grupos 4A, 4B e 5, com predominância de sua ausência. Este resultado pode ter contribuído para os melhores resultados funcionais dos grupos 1, 2 e 3; pois, considerando-se o aspecto evolutivo da classificação de Hamada, a cabeça longa do bíceps poderia atuar como depressor da cabeça umeral e impedir a progressão da artropatia, como evidenciam Garcia et al 14 em seu estudo de 2018. Com relação ao tendão subescapular, não houve diferença estatística significativa entre os grupos ( Tabela 2 ), o que leva a crer que este parâmetro não exerceu influência nos resultados funcionais dos ombros estudados.…”
Section: Discussionunclassified
“…Moreover, the Popeye deformity was 3 times more common in the tenotomy patients. Recently, García-Rellán et al 11 reported functional and strength improvements in both tenotomy and tenodesis patients. However, the elbow flexion strength of the patients submitted to tenotomy did not reach that of the contralateral side.…”
Section: Discussionmentioning
confidence: 99%
“…After performing the previous exercises, a submaximal isometric fatigue test (26,(28)(29)(30)(31)(32)(33) was used. This test consisted of performing a contraction in isometric flexion on 33% of the MVC obtained previously, and was maintained as long as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the authors of the biomechanical articles base their studies on the measurement of the peak force of elbow flexion or forearm supination, but this may not be the most interesting parameter to know the functional result of the surgery on de LHBT, given that most of the of daily tasks are performed by repeated submaximal contractions (25). This is why other authors have based their biomechanical analysis on the quantification of fatigue of the biceps after the surgery on the LHBT, demonstrating early fatigue in cases operated by tenotomy, with respect to the healthy arm (26). Therefore, a prospective randomized comparative clinical trial was designed analyzing biomechanical results of 2 different techniques for the treatment of the LHBT: tenotomy vs tenodesis.…”
Section: Introductionmentioning
confidence: 99%